Short-term outcome comparison of Norwood procedures with right ventricle to pulmonary artery conduit versus modified Blalock-Taussig shunt: A meta-analysis - Rohit Seth Loomba; Parinda Haresh Shah; Suraj Chandrasekar (Wolters Kluwer Medknow Publications, 2011)
A small number of nonrandomized and retrospective studies have compared outcomes of classical Norwood procedures for hypoplasticleft-heart syndrome and single ventricle lesions involving a Blalock-Taussig (BT) shunt to the modified procedure using a right ventricle to pulmonary artery conduit. Some of these studies reported data for the same outcomes and a meta-analysis was done to analyze pooled outcomes comparing in-hospital mortality, interstage mortality, cardiopulmonary bypass time, systolic and diastolic blood pressures 24 h postoperatively, length of intensive care and hospital stay, and need for postoperative extracorporeal membrane oxygenation. Right ventricle to pulmonary artery conduit was associated with an insignificant reduction of in-hospital mortality (odds ratio, 0.674, 95% confidence interval, 0.367 to 1.238), and in the length of hospital stay. There were significant reductions in cardiopulmonary bypass time, length of intensive care unit stay, and need for postoperative extracorporeal membrane oxygenation, postoperative ventilation times, and interstage mortality (odds ratio, 0.191, confidence interval, 0.0620 to 0.587). There was a significant increase in diastolic blood pressure and an insignificant increase in systolic blood pressure 24 h postoperatively. This pooled analysis demonstrates potential advantages associated with the right ventricle to pulmonary artery conduit when compared to the modified BT shunt in palliation and demonstrates the need for large randomized controlled trials that compare a number of outcomes in both procedures.